Edukasi Permainan Make a Match dengan ular tangga terhadap pengetahuan menjaga kesehatan gigi dan mulut: Edukasi - Femala, Dian; K.P, Anjarningrum; S, Rezki; Fathiah, Fathiah; Rusmali , Rusmali (JURNAL TERAPIS GIGI DAN MULUT, 2025)
Oral health education is crucial for children aged 6-12 years, as this is a critical period for dental growth and development. Creative and innovative education is essential to attract children's interest, as they are in a play-based phase of development. Many educational methods incorporate learning through play, and in this study, the Make a Match game was combined with a snakes and ladders board. The study aimed to determine the effect of the Make a Match game, aided by the snakes and ladders media, on improving knowledge of oral health. The method used was a quasi-experiment with a pretest-posttest control group design. The sample consisted of 94 students selected using purposive sampling. Data collection was followed by analysis using the Kruskal-Wallis test. The results showed that the average knowledge increase in the control group, which received a lecture, was 15.8%, the experimental group 1, which received the game, was 20.4%, and the experimental group 2, which received both a lecture and the game, was 38.86%. The asymp.sig value (p < 0.05) was 0.00, indicating a significant effect of the Make a Match game with the snakes and ladders media on improving oral health knowledge in experimental group 2. It can be concluded that there was a significant improvement in knowledge of oral health after the Make a Match game with snakes and ladders was introduced. Keyword : Education, Make A Match With Snake And Ladder, Knowledge, Maintaining Dental And oral Health